Assessment of prazifen on embryotoxic and teratogenic action - I. R. Salgiriyev; M. B. Musaev (Российский паразитологический журнал, 2016)
Prazifen in a dose of 1,0/10,0 and 3,0/30,0 mg/kg DV respectively on praziquantel and fenbendazole at introduction in stomach during the various periods of embryogenesis didn't show embryotoxic and teratogenic action.